A nanoclay-confined single atom catalyst: tuning uncoordinated N species for efficient water treatment. Issue 27 (27th June 2022) - Dong, Xiongbo; Qian, Yinyin; Chen, Zitong; Jiang, Zhiyi; Tang, Aidong; Yang, Huaming
Abstract : Uncoordinated nitrogen species in a single atom catalyst accelerate the release of intermediates and the regeneration of active sites via downshifting its d-band center to a lower energy level. Abstract : Optimizing the spatial coordination configuration of nitrogen-doped graphene-based single atom catalysts (NG-SACs) has been growing as a "hot" topic in water treatment. In NG-SACs, only a small part of the nitrogen takes part in single atom coordination. Whether the uncoordinated N species play significant roles in the spatial coordination configuration has been overlooked and little explored so far. Due to the lack of a tunable and predictable method for the synthesis of NG-SACs, it is still a great challenge to establish a correlation between uncoordinated N species, spatial coordination configuration and catalytic properties. In this work, we introduce a nanoclay confinement strategy to precisely control uncoordinated N species in NG-SACs. The NG-SACs show negligible differences in structural characterization except for the types of uncoordinated N species. Theoretical calculations indicate that uncoordinated graphitic N in NG-SACs has a downshifted d-band center of Mn versus pyridinic N. The lower energy level optimizes the bonding energy of intermediates on single atom centers, accelerating the release of intermediates and the regeneration of active sites. As a result, a higher ratio of uncoordinated graphitic N in NG-SACs leads to better peroxymonosulfate activation performance. The strategy proposed here can be extended to the tunable design of efficient NG-SACs for environmental remediation, and is also a controllable route for revealing other fundamental relationships between catalytic performance and local atomic environments of NG-SACs.